2017
DOI: 10.1080/00028487.2017.1281170
|View full text |Cite
|
Sign up to set email alerts
|

Safety of AQUI‐S 20E (10% Eugenol) as a Sedative for Freshwater Fish

Abstract: AQUI-S 20E (10% eugenol) has been shown to be an effective fish sedative for freshwater finfish, but to be approved for use in the United States, the U.S. Food and Drug Administration must be provided with data demonstrating the product is safe to treated animals. Accordingly, we evaluated the safety of AQUI-S 20E when used to sedate Rainbow Trout Oncorhynchus mykiss, Yellow Perch Perca flavescens, and Channel Catfish Ictalurus punctatus. After identifying the highest effective concentrations likely to be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
0
4
1
Order By: Relevance
“…Species that depend primarily or entirely on dissolved oxygen in the water are known to have shorter induction rates compared with air-breathing species (Hseu et al 1997;Neiffer and Stamper 2009), further supporting the conclusion that air breathing must be prevented when attempting sedation via immersion in gar. The dose of AQUI-S 20E required to induce stage 5 anesthesia in Shortnose Gar in our study was lower than that reported for Rainbow Trout, Yellow Perch, and Channel Catfish Ictalurus punctatus (Bowker et al 2017), while induction times were longer compared with other sedatives tested on other species (Bridger and Booth 2003;Ammann et al 2013;Wargo Rub et al 2014;Midwood et al 2018). In addition, recovery time was quick and comparable to other species that have been sedated using AQUI-S 20E (Javahery and Moradlu 2012), and we did not observe adverse reactions, such as prolonged recovery from sedation or short-term mortality.…”
Section: Sourcecontrasting
confidence: 67%
See 1 more Smart Citation
“…Species that depend primarily or entirely on dissolved oxygen in the water are known to have shorter induction rates compared with air-breathing species (Hseu et al 1997;Neiffer and Stamper 2009), further supporting the conclusion that air breathing must be prevented when attempting sedation via immersion in gar. The dose of AQUI-S 20E required to induce stage 5 anesthesia in Shortnose Gar in our study was lower than that reported for Rainbow Trout, Yellow Perch, and Channel Catfish Ictalurus punctatus (Bowker et al 2017), while induction times were longer compared with other sedatives tested on other species (Bridger and Booth 2003;Ammann et al 2013;Wargo Rub et al 2014;Midwood et al 2018). In addition, recovery time was quick and comparable to other species that have been sedated using AQUI-S 20E (Javahery and Moradlu 2012), and we did not observe adverse reactions, such as prolonged recovery from sedation or short-term mortality.…”
Section: Sourcecontrasting
confidence: 67%
“…One major benefit of AQUI‐S 20E is that wild‐caught fish can be immediately released after treatment (https://www.fws.gov/fisheries/aadap/inads/AQUI-S20E-INAD-11-741.html), permitting its use in field studies. AQUI‐S 20E has been shown to effectively sedate a wide variety of fishes to a “handleable” state (Bowker et al 2015, 2017); however, the effective dosage of AQUI‐S 20E for achieving stage 5 anesthesia (Summerfelt and Smith 1990) specifically in gars is unknown.…”
mentioning
confidence: 99%
“…As such, different countries have officially licensed eugenol as an aquatic anaesthetic with no withdrawal time (MCC (Medicines Control Council, South Africa), 2004; MPI (Ministry for Primary Industries of New Zealand), 2022) or with a withdrawal period set at 7 days (MAFF (Ministry of Agriculture, Forestry and Fisheries of Japan), 2015) although this compound is not currently FDA‐approved (FDA (Food and Drug Administration, United States of America), 2007) and no information could be found in European agencies. Yet, although other monoterpenes require further investigation, it is noteworthy that MS‐222 recommended withdrawal period varies from 21 (Bowker et al, 2019; FDA (Food and Drug Administration, United States of America), 2007) to 70 days (AQUAVET SA, 2022). Furthermore, MS‐222 is considered a local anaesthetic that blocks voltage‐gated sodium channels and prevents the development of nerve action potentials while not paralysing fish muscles (Attili & Hughes, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…After subsequent time periods varying in length from 10 min to 31 h postfeeding, we used gastric lavage to recover the remaining prey items. This involved the use of Aqui-S (Bowker et al 2017) as an anesthetizing agent and the use of a 60-cm 3 syringe fitted with a blunt, 18-gauge needle. Water was syringed into the stomach of each fish, and prey items were collected into a tray, filtered through a coffee filter (Melitta brand), and preserved in ethanol for inspection under a dissecting microscope.…”
Section: Methodsmentioning
confidence: 99%